EFFECT OF ASH CONTENT ON COAL QUALITY OF THE LABANAN FORMATION - Sugiarto, Wahyu; T. Listyani; Winarti (KURVATEK, 2023)
The ash content is a residual material from burning coal. The higher the ash content, the lower the coal quality value. This shows that the ash content affects the value of coal quality. The purpose of this study was to determine the effect of ash content on the calorific value of coal in the Labanan Formation. The research method used is drilling and laboratory analysis on each coal seam. The mean quality of the coal seam in the study area is total moisture 40.13%, innate moisture content 13.47%, ash content 4.57%, volatile matter 42.61%, solid carbon 39.35%, total sulfur content 0.18 % and calorie value 5427 Kcal/kg (ADB). Based on the caloric value parameter, the research area is classified as low-calorie coal (brown coal). Keywords: Ash, coal quality, Labanan Formation